1999
DOI: 10.1523/jneurosci.19-07-02823.1999
|View full text |Cite
|
Sign up to set email alerts
|

Central Neuronal Circuit Innervating the Lordosis-Producing Muscles Defined by Transneuronal Transport of Pseudorabies Virus

Abstract: The lordosis reflex is a hormone-dependent behavior displayed by female rats during mating. This study used the transneuronal tracer pseudorabies virus (PRV) to investigate the CNS network that controls the lumbar epaxial muscles that produce this posture. After PRV was injected into lumbar epaxial muscles, the time course analysis of CNS viral infection showed progressively more PRV-labeled neurons in higher brain structures after longer survival times. In particular, the medullary reticular formation, periaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 64 publications
10
56
0
Order By: Relevance
“…Additionally, estrogen receptor-containing neurons are found specifically in the vlVMH (Pfaff and Keiner, 1973;Simerly et al, 1990;DonCarlos et al, 1991). Moreover, the descending projections of the ventrolateral but not the dorsal VMH target the ventrolateral periaqueductal gray (Canteras et al, 1994), the subdivision thought to be involved in the lordosis posture (Lonstein and Stern, 1998;Daniels et al, 1999). Although the regional specificity of estrogen-induced spines in the VMH implicates them in sexual behavior, it remains to be established whether these spines represent legitimate synapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, estrogen receptor-containing neurons are found specifically in the vlVMH (Pfaff and Keiner, 1973;Simerly et al, 1990;DonCarlos et al, 1991). Moreover, the descending projections of the ventrolateral but not the dorsal VMH target the ventrolateral periaqueductal gray (Canteras et al, 1994), the subdivision thought to be involved in the lordosis posture (Lonstein and Stern, 1998;Daniels et al, 1999). Although the regional specificity of estrogen-induced spines in the VMH implicates them in sexual behavior, it remains to be established whether these spines represent legitimate synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, receptor autoradiography, immunocytochemistry, and in situ hybridization have demonstrated the presence of estrogen receptors in the VMH (Pfaff and Keiner, 1973;Simerly et al, 1990;DonCarlos et al, 1991). Moreover, transneuronal tracing studies have confirmed the serial connectivity of the VMH to the lumbar epaxial muscles that execute the stereotypic female reproductive posture, lordosis (Daniels et al, 1999). Nevertheless, key questions remain about the microcircuitry within the VMH and how estrogen may alter neural connectivity to control the expression of this behavior.…”
Section: Abstract: Dendritic Spines; Estrogen; Female Sexual Behaviomentioning
confidence: 99%
“…When the female is in estrus, i.e. when estradiol concentrations are high, several brain regions including the ventrolateral portion of the VMN (a brain region rich in estrogen receptors) and the MPN, activate via the midbrain central gray, medullary reticular formation, and medial geniculate body, the spinal motoneurons innervating the back muscles critical to the display of lordosis [23]. Thus, the VMN plays a critical role in integrating hormonal and sensory information necessary for the display of lordosis in female rodents.…”
Section: Neural Mechanisms Potentially Affected In Female Arko Micementioning
confidence: 99%
“…Although classical theories regarding autonomic and motor control suggest that these systems are quite disparate (Cannon, 1963), there are numerous examples of behaviors that are characterized by coordinated motor and autonomic regulation, including exercise, startle, defense ("fight-or-flight") reaction, pain responses, reproductive behavior (lordosis), vocalization, righting reflexes, feeding, micturition, and sleep (Hilton, 1982;Eldridge et al, 1985;Lovick, 1991;Daniels et al, 1999;Palmer and Printz, 1999;Kerman et al, 2000a,b). For instance, locomotion and exercise require intermittent and complementary contractions of synergistic muscle groups and simultaneous activation of autonomic and respiratory systems to increase cardiac output and to redistribute blood flow from skin and viscera to contracting muscles (Waldrop et al, 1996).…”
Section: Introductionmentioning
confidence: 99%